Perspective of clinical application of pumpless extracorporeal lung assist (ECMO) in newborn - Gandolfi José Francisco (Brazilian Journal of Cardiovascular Surgery, 2003)
Extracorporeal lung assist (ECLA) has been proposed as an invasive alternative to conventional treatment when oxygenation is not possible by rigorous mechanical ventilation alone. Usually, ECLA is carried out by establishing a venovenous or venoarterial shunt consisting of a roller or centrifugal pump, a membrane oxygenator, and a heat exchanger. However, the extracorporeal membrane oxygenation (ECMO) with circulatory support lead hemolysis, coagulation disorders, inflammatory response, and specific technical complications inherent to a procedure of high risk and cost. To reduce the drawbacks of mechanical blood trauma during prolonged ECLA, the patient´s arteriovenous pressure gradient as the driving force for the blood flow through for the extracorporeal circuit can be used. In this article are analysed the main contributions of pumpless ECMO, used experimentally and in children and adults with respiratory failure, with perspective of clinical application in newborn.